Perkawinan Usia Dini : Kajian Sosiologis Tentang Struktur Sosial Di Desa Pengotan Kabupaten Bangli - Santhy Devi, Putu (JURNAL ILMIAH SOSIOLOGI (SOROT), 2012)
The marital of the community in the Pengotan Village of Bangli Regency , were set in an awig awig that should be carried out in bulk . The disadvantages of this mass marriage system, led to the occurrence of early marriages because of the awig awig are not expressly required the age limit. The problems which are examined in this studies are as follows : (1) How to organize the social structures of early marriages in the Pengotan Village ? (2) How does the influence of the early marriages to the socio-economic life of the family ? The approach system used in this study is a qualitative method which is conducted in the Pengotan Village . The basic of the research is a case study , while the type of research used is descriptive method that aims to describe the social structure’s relationships in the mass wedding ceremony . The theoretical background that is used in this research is the social action in which there were a component of the social structure. The results of this study indicate that the mass marriage that should be carried out in the Pengotan Village are not explicitly mention the age limits and thus indirectly legitimize the occurrence of early marriages. There are also the cause of the other factors such as : 1) their own accord, 2) economic hardship, 3) lack of education, and 4) pregnancy out of marriage . Early marriages certainly affects the home life. In terms of the economyc factors, where the early age couples do not have the skills so that their income is just enough for their daily needs. While in the terms of social factors, the early age couples of marriages are often encounters the role dysfunctions.